Management research - Batra, G. S. (New Delhi : Anmol Publications, 1995)
Collection of research papers on business management practices, policies, and emerging trends, particularly in India.
Includes bibliographical references.
Rashid
Keywords: Management -- India; Executives -- Training of -- India